2021
DOI: 10.1155/2021/3387742
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infections and Associated Risk Factors among Pregnant Women Attending Prenatal Care in the Northwestern Ethiopia

Abstract: Intestinal parasitic infections (IPIs) are the common health problems in developing countries with low socioeconomic and poor living conditions. IPIs affect millions of pregnant women worldwide and may lead to adverse maternal and fetal effects. The present study was aimed at determining the prevalence and associated risk factors of IPIs among pregnant women in Ethiopia. A hospital-based cross-sectional study involving 384 pregnant women was conducted from November 2018 to March 2019. Relevant information on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Our data confirmed that the peoples with no formal education had 3.71 times (adjusted OR: 3.71, 95% CI: 1.35–7.471, p = 0.038) higher odds of IPIs when compared to those who attended any formal education. This finding confirm the conclusion made in priory study in Ethiopia [ 63 ] and the finding suggest the importance of awareness creation to prevent further transmission of IPI among illiterate individuals though this was not addressed in these studies. Analysis of result by fingernail status showed that regular trimming of figure nail was associated with an approximately 40% lower odds of any intestinal parasitic infections (adjusted OR: 0.60 (95%CI: 0.11 to 0.90)).…”
Section: Discussionsupporting
confidence: 84%
“…Our data confirmed that the peoples with no formal education had 3.71 times (adjusted OR: 3.71, 95% CI: 1.35–7.471, p = 0.038) higher odds of IPIs when compared to those who attended any formal education. This finding confirm the conclusion made in priory study in Ethiopia [ 63 ] and the finding suggest the importance of awareness creation to prevent further transmission of IPI among illiterate individuals though this was not addressed in these studies. Analysis of result by fingernail status showed that regular trimming of figure nail was associated with an approximately 40% lower odds of any intestinal parasitic infections (adjusted OR: 0.60 (95%CI: 0.11 to 0.90)).…”
Section: Discussionsupporting
confidence: 84%
“…However, several studies demonstrated the very high prevalence of IPIs among pregnant women. For instance, the overall prevalence of IPIs among pregnant women attending ANC in Yifag Health Center, Northwest Ethiopia, was 53.4% [ 18 ]; that among pregnant women in West Gojjam Zone, Northwest Ethiopia, was 37.3% [ 19 ]; that among pregnant women attending prenatal care at Felege Hiwot Referral Hospital, Bahir Dar, was 31.5% [ 15 ]; that among pregnant women attending prenatal care in the Northwestern Ethiopia was 36.7% [ 20 ]; that among pregnant women in the Wondo Genet District, Southern Ethiopia, was 38.7% [ 16 ]; and that among pregnant women attending ANC at public health facilities in the Lalo Kile District, Oromia, Western Ethiopia, was 43.8% [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to a prevalence of 66.7% reported in Burkina Faso [ 102 ]. In contrast, lower prevalences have been reported in Ghana (14.3%), Kenya (13.8%), or Ethiopia (27.32%) [ 103 , 104 , 105 ]. A. duodenale was among the most frequent type of parasite in this group.…”
Section: Discussionmentioning
confidence: 99%